The Climate Change Alliance: botanic garden horticulturists as agents for change - Symes, Peter; Hart, Clare (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2021)
In 2016, the publication of the pioneering Landscape Succession Strategy heralded a horticultural response by Royal Botanic Gardens Victoria to climate change risks faced by their living collections. This initiative led to the botanical world’s first Climate Change Summit in 2018 and the subsequent establishment of the Climate Change Alliance for Botanic Gardens. This article describes some of the anticipated climatic changes facing the Melbourne Gardens site, the strategic management of collections when considering these challenges, and how other botanical organisations can benefit from this approach through collaboration and sharing of expertise.